Het Apollohuis 1995-2001 - Panhuysen, Paul; Zijlmans, Kitty; Coenen, André; Manders, Chris; Sachsse, Rolf; Yocarini, Titus; Johnson, Tom; Bull, Hank; Brand, Jens; Adriaans, René; Peer, René van; Voort, Mark van de; et al. (Eindhoven Het Apollohuis, 2002)
Het Apollohuis (English: The Apollo House) was a space for experimental music and visual arts, "focused in particular on...sound art, new music, performance art and the new media," founded in Eindhoven, Netherlands, by Remko Scha and Paul Panhuysen in a former 19th century cigar factory in 1980. Partly funded by their own publishing house, the space was closed in 2001 after their grant was discontinued."Between 1980 and 2001, Het Apollohuis organized 253 art exhibitions, 476 concerts and performances, 46 public lectures, symposia and several festivals (as "ECHO: images of sound II" in 1987 [2] or FLEA Festival in 1997). Artists-in-residence, asked to create an exhibition, an installation or a publication, where provided with an apartment, studio space, and materials. Known artists that had events at the Apollohuis were for instance Ellen Fullman, Glenn Branca, Michel Waisvisz, Pauline Oliveros, Pierre Bastien, The Hub (band), Nicolas Collins, Maciunas Ensemble.
Keywords: Het Apollohuis; Exhibition; Performance art; Concert; Cuckoo